Guideline for treating hepatitis B virus infection in Bangladesh - Rahman, Salimur; Al-Mahtab, Mamun; Karim, Md Fazal (Bangladesh Liver Journal, 2009)
Over 350 million people worldwide are infected with Hepatitis B virus (HBV) and globally around 1 million die due to consequences of this infection annually. Bangladesh belongs to the intermediate prevalence region for HBV infection. Here the lifetime risk of acquiring HBV is between 20-60%. Studies from our as well as other groups have shown that HBV is responsible for 31.25% cases of acute hepatitis, 76.3% cases of chronic hepatitis, 61.15% cases of cirrhosis of liver and 33.3% cases of hepatocellular carcinoma (HCC) in Bangladesh. doi: 10.3329/blj.v1i1.2619 Bangladesh Liver Journal Vol.1(1) 2009 p.6-12